Hydrogels derived from acellular porcine corneal stroma enhance corneal wound healing. (15th October 2021) - Zhou, Qiang; Guaiquil, Victor H.; Wong, Matthea; Escobar, Alejandro; Ivakhnitskaia, Evguenia; Yazdanpanah, Ghasem; Jing, Hongwu; Sun, Michael; Sarkar, Joy; Luo, Yuncin; Rosenblatt, Mark I.
Abstract: Acellular cornea derived hydrogels provide significant advantages in preserving native corneal stromal keratocyte cells and endothelial cells. However, for clinical application, hydrogel physical properties need to be improved, and their role in corneal epithelial wound healing requires further investigation. In this study, an acellular porcine corneal stroma (APCS) hydrogel (APCS-gel) was successfully prepared from 20 mg/ml APCS, demonstrated optimal light transmittance and gelation kinetic properties and retained critical corneal ECM of collagens and growth factors. Compared with fibrin gel, the APCS-gel had a higher porosity ratio and faster nutrition diffusion with an accompanying improvement in the proliferation of primary rabbit corneal epithelial cells (RCECs) and stromal cells (RCSCs). These corneal cell types also displayed improved viability and cellular infiltration. Furthermore, the APCS-gel provides significant advantages in the preservation of RCECs stemness and enhancement of corneal wound healing in vitro and in vivo . After 7 days of culture, 3-4 layers of RCECs were formed on the APCS-gel in vitro, while only 1-2 layers were found on the fibrin gel. More corneal stem/progenitor cell phenotypes (K12-, p63+, ABCG2+) and proliferation phenotypes (Ki67+) were detected on the APCS-gel than fibrin gel. Using a corneal epithelial wound healing model, we also found faster reepithelization in corneas that received APCS-gel compared to fibrin gel. Additionally, our APCS-gel demonstrated better physical and biological properties when compared to Tisseel, a clinically used type of fibrin gel. In conclusion, our APCS-gel provided better corneal epithelial and stromal cell biocompatibility to fibrin gels and due to its transparency and faster gelation time could potentially be superior for clinical purposes. Statement of significance: Extracellular matrix (ECM) can be used to provide tissue specific physical microstructure and biochemical cues for tissue regeneration. Here, we produced an ECM hydrogel derived from acellular porcine cornea stroma (APCS-gel) that retained critical biological characteristics of the native tissue and provided significant transparency and fast gelation time. Our data demonstrated that the APCS-gel was superior to clinically used fibrin gel, as the APCS-gel showed high porosity and permeability, better corneal stromal keratocytes infiltration, increased cellular proliferation and retention of corneal epithelial cells stemness. The APCS-gel improved corneal wound healing in vitro and in vivo . This APCS-gel may have clinical utility for corneal diseases, and the more general approach used to make this hydrogel might be used in other tissues. Graphical abstract: Image, graphical abstract